EXPERIMENTAL AND NUMERICAL STUDY RETROFITTING BEAM WITH EXPANSION IN THE SUPPORT AREA - Purba, Luki Hariando; Lisantono, Ade (Politeknik Negeri Semarang, 2025)
Retrofitting is one way to strengthen a building to withstand earthquakes and is often called an earthquake-resistant structure. Retrofitting beams will increase strength, stiffness, and ductility so that the structure is still stable when experiencing large earthquake forces. In addition to experimental methods, numerical methods are also used by researchers in developing a study of the behavior of building structures. Numerical methods using finite element software can examine the behavior of strength, stiffness, and ductility in beams. With this background, the author conducted a study of the retrofitting behavior of beams that were widened in the support area using numerical methods and theoretical analysis. The purpose of this study has been achieved so that a conclusion can be given that retrofitting with widening in the beam support area can increase the beam capacity quite significantly. Based on numerical research, with wide expansion reinforcement in the cross-sectional dimensions, the beam strength is increased by almost 45% and the beam stiffness is increased by 13-40% while ductility does not show a significant difference. These results are also expected to show the same behavior in experimental testing so that it will strengthen this reinforcement method. Experimental and numerical testing will be conducted in this study so that it will maintain the results and it is hoped that they can be accepted and practiced in the world of building construction.